Digital Marketing Strategies for attract Millenial Travelers to Hotel Santika Premiere ICE BSD City - Rosim; Siswara, Githa; Suwarta, Firdaus (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
This study analyzes digital marketing strategies for attract millennial travelers (aged 25–40) to Hotel Santika Premiere ICE BSD City, based on trends for 2024–2025. The background is rooted in the dominance of millennials in the domestic travelers market (72% rely on digital recommendations) and the urgency of digital transformation post-pandemic. A descriptive qualitative method through case study was employed, with data collection techniques including in-depth interviews (5 informants: marketing manager, social media staff, millennial guests), participatory observation, and document analysis. The research findings indicate that the MySantika app is the key driver behind a 30% increase in direct bookings, with three critical features: Exclusive Discounts (25% interest vs. OTAs), leveraged through Ramadan promotions (10% discount & free breakfast), Digital Check-in/out (15% guest satisfaction), saving 5 minutes of waiting time through OTP verification and PMS integration, and Personalized Recommendations based on machine learning (20% conversion rate), tailored to room preferences and nearby activities. Supporting strategies include Instagram visual content optimization (Reels/Stories with 40% engagement), Collaboration with local influencers (live session Santai Sore Ramadhan), integration of digital payment methods (OVO / QRIS / PayLater). The main challenges are the limited features of MySantika for the international market and dependence on internet connectivity. Recommended solutions include expanding the global loyalty program and developing an offline mode feature. The research conclusion emphasizes that the combination of mobile apps, interactive content, and personalization is an effective strategy to reach millennials. The practical implication encourages continuous technology-based innovation to sustain growth in the digital era.